OPTIMIZING CONSUMER SATISFACTION THROUGH THE IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE, GREEN CONSUMER BEHAVIOR, AND GREEN MARKETING IN THE DISTRIBUTION OF TAPIS LAMPUNG FASHION PRODUCTS - Putri Anggraini Lestari; Lestari Wuryanti; Ayu Nursari (International Journal of Management, Economic and Accounting, 2026)
The rapid advancement of digital technology has transformed marketing and product distribution practices, including in the local fashion industry, where digital innovations are increasingly adopted to enhance business competitiveness. At the same time, growing public awareness of environmental issues has encouraged consumers to consider sustainability aspects when making purchasing decisions. This study aims to examine the influence of Artificial Intelligence (AI) implementation, green consumer behavior, and green marketing on consumer satisfaction in the distribution of Tapis Lampung fashion products. A quantitative research approach was employed by distributing questionnaires to consumers of Tapis Lampung fashion products. The collected data were analyzed using multiple linear regression, supported by validity, reliability, classical assumption, partial (t-test), simultaneous (F-test), and coefficient of determination analyses. The findings indicate that Artificial Intelligence implementation, green consumer behavior, and green marketing have positive and significant effects on consumer satisfaction, both individually and simultaneously. These results suggest that integrating digital technology with sustainable marketing strategies improves distribution performance, strengthens consumer perceptions, and enhances overall satisfaction with Tapis Lampung fashion products.